2000
DOI: 10.7153/mia-03-26
|View full text |Cite
|
Sign up to set email alerts
|

The best bounds in Gautschi's inequality

Abstract: Abstract. Different approach to both Gautschi's inequalities (1) and (2) is given. This results in obtaining the best upper bound in (1) and the best lower bound in (2). The main result is the proof of the convexity of the function [Γ(x+t)/Γ(x+s)] 1/(t−s) for |t−s| < 1 . Several new very simple inequalities for digamma function, like ψ (x) < exp(−ψ (x)) or ψ (x + 1) < log(x + e −γ ) are also proved.Mathematics subject classification (1991): 33B15, 26D07.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 8 publications
0
60
0
Order By: Relevance
“…for example [EGP00]). We also use that be the number of arithmetic operations required to perform i loops of the algorithm.…”
Section: γ(N)mentioning
confidence: 99%
“…for example [EGP00]). We also use that be the number of arithmetic operations required to perform i loops of the algorithm.…”
Section: γ(N)mentioning
confidence: 99%
“…The required inequality (1.3) follows from the fact that the sequence Q n (α) is strictly decreasing. This, in turn, is an immediate consequence of a result of N. Elezović, C. Giordano and J. Pecarić, [8] who showed that the function This completes the proof of (1.3).…”
Section: Proof Of (13)mentioning
confidence: 54%
“…In order to establish the best bounds in Kershaw's inequality (1), among other things, the papers [3,5,13,18] established the following monotonicity and convexity property of z s,t (x): The function z s,t (x) is either convex and decreasing for |t − s| < 1 or concave and increasing for |t − s| > 1. This result was further generalized in the papers [10,11].…”
Section: That L[i] ⊂ C[i]mentioning
confidence: 99%